Reinterpretasi Makna Jihad dalam Al-Qur’an dan Hadis: Upaya Kontekstualisasi di Masa Kini - Khaerul Umam (MADINAH, 2024)
The aim of this research is to gain knowledge about the concept of the true meaning of jihad. Using qualitative methods supported by literature review with various stages containing content analysis. With the final result stating that Jihad in Islam has a broad and deep meaning. Etymologically, jihad comes from the Arabic word "جَهَدَ" which means trying seriously. M. Quraish Shihab explained that jihad includes the meaning of difficulties, tests, abilities, and struggle against Satan and lust, supported by verses from the Koran such as Q.S. ali-Imran: 142 and Q.S. al-Baqarah: 214. Jihad is divided into fardhu 'ain and fardhu kifayah. Fardhu 'ain is an individual obligation in critical situations, such as direct war, while fardhu kifayah is a collective obligation which if some people have carried it out, others are free from this obligation. Scholars such as Yusuf Qardhawi and Hassan al-Banna stated that jihad includes defending the truth, securing preaching, and fighting oppression, as well as aspects of education, politics, and material sacrifice. In the modern era, jihad against lust and the search for knowledge has become relevant as an important form of struggle to build a moral and knowledgeable society